PENERAPAN DIGITAL MARKETING MELALUI MEDIA SOSIAL DI SMK TEUKU UMAR - Ade Mardiansyah; Aldo; Damas Aryanto; Endru Yuda Muslim; Frans Liman Dibrata; Giardo Nur Alfajianzah; Irsyad Ikhsanudin; Muhamad Fauzi; Rizqi Maulana; Yudha Febriansyah (Abdi Jurnal Publikasi, 2022)
The rapid development of today's social media is caused by everyone who feels like they can